Teaching Vocabulary To The Fourth Grade Students Of SDN II Sumberagung, Batuwarno, Wonogiri In 2011/2012 Academic Year - Asih, Hesti Ratna (2012)
This research aims at describing teaching vocabulary to the fourth grade students of SDN II Sumberagung, Batuwarno, Wonogiri. The objectives of this research paper are to describe: (1) process of vocabulary teaching-learning at fourth grade students of SDN II Sumberagung, Batuwarno, Wonogiri, (2) the problems faced by the teacher, (3) problem solving applied by the teacher with appropriate method. The type of this research is descriptive qualitative. The subject of this research is English teacher and the fourth grade students of SDN II Sumberagung, Batuwarno, Wonogiri. The object of this research is vocabulary teaching-learning process in SDN II Sumberagung, Batuwarno, Wonogiri. The Writer uses descriptive method as method of collecting data in this study by employing observation, interview, and document. Based on the result of the analy sis, the writer finds the process of teaching vocabulary to the fourth grade students of SDN II Sumberagung, Batuwarno, Wonogiri that are the materials used by the teacher are worksheet and handout. The media used by the teacher are picture, board, and real condition. The techniques used by the teacher are repetition, memorization, sing a song, discussion, pair work, matching the words with the appropriate meaning and arranging the letters. While the evaluation used by teacher through test and non test. The problems faced by the teacher are the different competence, the different character, the influence of environment, and the media. To solve the first problem are always used drilling, repetition, combining the interesting media and always motivates the students who have low capability, given more attention and more explanation about the material. To solve the second problem is the teacher will be give more attention to the students' trouble maker calmly and give question. And to solve the third problem is usually reviews about the previous material.